Increasing active travel: results of a quasi-experimental study of an intervention to encourage walking and cycling. Issue 12 (1st June 2015) - Keall, Michael; Chapman, Ralph; Howden-Chapman, Philippa; Witten, Karen; Abrahamse, Wokje; Woodward, Alistair
Abstract : Background: There is increased interest in the effectiveness and cobenefits of measures to promote walking and cycling, including health gains from increased physical activity and reductions in fossil fuel use and vehicle emissions. This paper analyses the changes in walking and cycling in two New Zealand cities that accompanied public investment in infrastructure married with programmes to encourage active travel. Method: Using a quasi-experimental two-group pre–post study design, we estimated changes in travel behaviour from baseline in 2011 to mid-programme in 2012, and postprogramme in 2013. The intervention and control cities were matched in terms of sociodemographic variables and baseline levels of walking and cycling. A face-to-face survey obtained information on walking and cycling. We also drew from the New Zealand Travel Survey, a national ongoing survey of travel behaviour, which was conducted in the study areas. Estimates from the two surveys were combined using meta-analysis techniques. Results: The trips and physical activity were evaluated. Relative to the control cities, the odds of trips being by active modes (walking or cycling) increased by 37% (95% CI 8% to 73%) in the intervention cities between baseline and postintervention. The net proportion of trips made by active modes increased by about 30%. In terms of physical activity levels, there was little evidence of an overall change. Discussion: Comparing the intervention cities with the matched controls, we found substantial changes in walking and cycling, and conclude that the improvements in infrastructure and associated programmes appear to have successfully arrested the general decline in active mode use evident in recent years.